2012
DOI: 10.1021/ef3003922
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bio-oils Produced from Fast Pyrolysis of Corn Stalks in an Auger Reactor

Abstract: Corn stalks were converted to bio-oils by fast pyrolsis in an auger fed reactor at 400 and 450 °C. Both acidpretreated and untreated corn stalks were pyrolyzed. Proximate and ultimate analyses of the corn stalk feeds and bio-oils were performed, and the bio-oils were characterized by gas chromatography/mass spectrometry (GC/MS), gel permeation chromatography (GPC), 13 C and 1 H NMR spectroscopy, pH, ash, and viscosity measurements, and solids content and water analyses. Corn stalks have lower lignin content th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 70 publications
0
36
0
1
Order By: Relevance
“…In a previous study, Pittman et al (2012) found that the 3.0 to 4.2 ppm range of the 1 H spectrum was related to the methoxy content. As shown in Fig.…”
Section: H Nmr Analysis Of Bio-oil Samples From Multistep Extractionmentioning
confidence: 91%
“…In a previous study, Pittman et al (2012) found that the 3.0 to 4.2 ppm range of the 1 H spectrum was related to the methoxy content. As shown in Fig.…”
Section: H Nmr Analysis Of Bio-oil Samples From Multistep Extractionmentioning
confidence: 91%
“…The main reasons for the high acetic acid concentration in this study would lie in on one hand that the feed material in this study was corncob which was abundant in hemicelluloses that could produce acetic acid by deacetylation during pyrolysis, and the other hand that the fast pyrolysis was conducted at lower reaction temperatures where lignin fraction of corncob could not be sufficiently devolalitized to be components of bio-oil. A recent study on the fast pyrolysis of corn stalk in a fluidized-bed reactor reported that the bio-oil contained 27.3% acetic acid (Pittman et al, 2012). The furfural concentration in the bio-oils was between 3.5 and 5.5 wt%, showing the maximum yield obtained at 357°C.…”
Section: Bio Oilmentioning
confidence: 99%
“…The pyrolysis behaviors of a variety of agricultural wastes, such as apple pomace (Baray et al 2014), hardwood residues (Mazlan et al 2015), corn stalk (Pittman et al 2012), peanut shells (Yao et al 2016a), grape residues (Xu et al 2009), rice husk and straw (Worasuwannarak et al 2007), wheat and corn straw (Lanzetta and Di Blasi 1998), and cherry seeds (Duman et al 2011), have been investigated for different purposes. Miura and Maki (1998) and Arora et al (2009) have focused on developing mathematical dynamic models for predicting the pyrolysis characteristics of various biomass wastes.…”
Section: Introductionmentioning
confidence: 99%